Intestine microbiota and SCFAs response in naturally Cryptosporidium-infected plateau yaks - Dong, Hailong; Chen, Xiushuang; Zhao, Xiaoxiao; Zhao, Chenxi; Mehmood, Khalid; Kulyar, Muhammad Fakhar-e-Alam; Bhutta, Zeeshan Ahmad; Zeng, Jiangyong; Nawaz, Shah; Wu, Qingxia; Li, Kun (Frontiers in Cellular and Infection Microbiology, 2023)
Diarrhea is a severe bovine disease globally prevalent in farm animals with a decrease in milk production and a low fertility rate. Cryptosporidium spp. are important zoonotic agents of bovine diarrhea. However, little is known about microbiota and short-chain fatty acids (SCAs) changes in yaks infected with Cryptosporidium spp. . Therefore, we performed 16S rRNA sequencing and detected the concentrations of SCFAs in Cryptosporidium-infected yaks. Results showed that over 80,000 raw and 70,000 filtered sequences were prevalent in yak samples. Shannon (p<0.01) and Simpson (p<0.01) were both significantly higher in Cryptosporidium-infected yaks. A total of 1072 amplicon sequence variants were shared in healthy and infected yaks. There were 11 phyla and 58 genera that differ significantly between the two yak groups. A total of 235 enzymes with the significant difference in abundance (p<0.001) were found between healthy and infected yaks, KEGG L3 analysis discovered that the abundance of 43 pathways was significantly higher, while 49 pathways were significantly lower in Cryptosporidium-infected yaks. The concentration of acetic acid (p<0.05), propionic acid (p<0.05), isobutyric acid(p<0.05), butyric acid (p<0.05), and isovaleric acid was noticeably lower in infected yaks, respectively. The findings of the study revealed that Cryptosporidium infection causes gut dysbiosis and results in a significant drop in SCFAs concentrations in yaks with serve diarrhea, which may give new insights regarding the prevention and treatment of diarrhea in livestock.